2022
DOI: 10.21814/childstudies.4126
|View full text |Cite
|
Sign up to set email alerts
|

Child studies through the lens of applied family social systems theory

Abstract: The foundations of an applied family social systems theory for explaining the multiple determinants of child well-being, learning, and development, parenting beliefs, behavior and practices, and family well-being are described. The theory is derived from tenets of Bronfenbrenner’s ecological systems theory and other social, family, and contextualized theories. The applied theory was used to develop an activity setting model of young children’s everyday learning opportunities and a family systems intervention p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
4
10
0
Order By: Relevance
“…The results reported in this paper, as well as findings reported elsewhere (e.g., [ 49 , 51 , 54 , 55 , 58 ]), are all consistent with the basic tenets of the applied family systems model [ 45 , 46 ] that guided the conduct of the research. The results provide support for the use of family strengths to obtain both resources and supports to achieve needs satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results reported in this paper, as well as findings reported elsewhere (e.g., [ 49 , 51 , 54 , 55 , 58 ]), are all consistent with the basic tenets of the applied family systems model [ 45 , 46 ] that guided the conduct of the research. The results provide support for the use of family strengths to obtain both resources and supports to achieve needs satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…The results also showed that both the family systems practices and the parents’ psychological health measures were related to the three parenting quality measures (Aims 2 and 3). These results are consistent with the foundations of the applied family systems theory that guided the conduct of meta-analyses [ 46 ]. This pattern of results is also consistent with Bronfenbrenner’s [ 41 ] assertations that parents are not able to carry out child-rearing responsibilities without adequate supports and resources that provide them the time and psychological energy to engage their children in development-enhancing learning activities and employ positive parenting practices.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…From a sociocultural and systemic approach [ 1 , 2 , 3 , 4 ], child development is conceptualized as a process that is intrinsically linked to the characteristics of the contexts in which it occurs and to the interpersonal processes that take place in these contexts. More specifically, from these systemic and interactive models, it is proposed that child development is the product of interaction of children with their parents and other primary caregivers in daily routines [ 4 , 5 , 6 ]. From this point of view, it is claimed that variability in child development can be explained not only by children’s individual constitutional characteristics but also by quality of parenting.…”
Section: Introductionmentioning
confidence: 99%